Deciphering Human Cell-Autonomous Anti-HSV-1 Immunity in the Central Nervous System - Lafaille, Fabien G.; Ciancanelli, Michael J.; Studer, Lorenz; Smith, Gregory; Notarangelo, Luigi; Casanova, Jean-Laurent; Zhang, Shen-Ying (Frontiers in Immunology, 2015)
Herpes Simplex Virus-1 (HSV-1) is a common virus that can rarely invade the human central nervous system (CNS), causing devastating encephalitis. The permissiveness to HSV-1 of the various relevant cell types involved in the disease, neurons, astrocytes, oligodendrocytes and microglia cells, as well as their response to viral infection, have been extensively studied in mice. Nevertheless, human CNS cell-based models of anti-HSV-1 immunity are of particular importance as responses to any given neurotropic virus may differ between humans and animals. Human CNS neurons cell lines as well as primary human CNS neurons, astrocytes and microglia cells cultured/isolated from embryos or cadavers, have enabled the study of cell-autonomous anti-HSV-1 immunity in vitro. However, the paucity of biological samples and their lack of purity have hindered progress in the field, which furthermore suffers from the absence of testable primary human oligodendrocytes. Recently, we have established a human induced pluripotent stem cells (hiPSCs)-based model of anti-HSV-1 immunity in neurons, oligodendrocyte precursor cells, astrocytes and neural stem cells, which has both widened the scope of possible in vitro studies, while permitting in-depth explorations. This mini-review summarizes the available data on human primary and iPS-derived CNS cells for anti-HSV-1 immunity. HiPSC-mediated study of antiviral immunity in both healthy controls and patients with HSV-1 encephalitis will be a powerful tool in dissecting the disease pathogenesis of CNS infections with HSV-1 and other neurotropic viruses.